2017
DOI: 10.1002/acr.23133
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Bone Erosion in Rheumatoid Arthritis by Denosumab: A High‐Resolution Peripheral Quantitative Computed Tomography Study

Abstract: Inhibition of receptor activator of NF-κB ligand by denosumab can induce partial repair of erosions in patients with RA, while erosions continued to progress in patients treated with alendronate. Combining denosumab with disease-modifying antirheumatic drugs may be considered for RA patients with progressive bone erosions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 40 publications
(59 reference statements)
0
50
2
Order By: Relevance
“…Monitoring these individual small cortical interruptions might be useful in understanding the pathogenesis of RA and might also be of value for evaluating the progression of structural damage or responsiveness to treatment in individual patients with RA. Previous research demonstrated, for example, repair processes of existing large pathological interruptions with HR‐pQCT in those patients using tumor necrosis factor inhibitors, interleukin‐6, or receptor activator of nuclear factor kappa B ligand (RANKL) blockers …”
Section: Discussionmentioning
confidence: 99%
“…Monitoring these individual small cortical interruptions might be useful in understanding the pathogenesis of RA and might also be of value for evaluating the progression of structural damage or responsiveness to treatment in individual patients with RA. Previous research demonstrated, for example, repair processes of existing large pathological interruptions with HR‐pQCT in those patients using tumor necrosis factor inhibitors, interleukin‐6, or receptor activator of nuclear factor kappa B ligand (RANKL) blockers …”
Section: Discussionmentioning
confidence: 99%
“…The details of the methodology have been published before . Briefly, the second metacarpal head (MC2) of the non‐dominant hand were examined by HR‐pQCT (XtremeCT; Scanco Medical AG, Bruttisellen, Switzerland) at baseline and at 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the second metacarpal head (MC2) of the non‐dominant hand were examined by HR‐pQCT (XtremeCT; Scanco Medical AG, Bruttisellen, Switzerland) at baseline and at 12 months. The MC2 is the most frequently affected metacarpal head in RA when assessed by ultrasound or micro‐CT . Therefore, assessment was confined to the MC2 region to optimize time efficiency and minimize motion artefact.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies documented a potent effect of DMab on bone erosion and bone mineral density (BMD) in RA (Table 1). In addition, high-resolution quantitative computed tomography studies performed on RA patients revealed partial bone repair (decrease depth, width and volume of erosions) was noted after 6 months of treatment with DMab but not alendronate (110). …”
Section: Dmab In Ramentioning
confidence: 99%